Towards the mature ePortfolio: Some implications for higher education - Diana Challis (The Canadian Network for Innovation in Education (CNIE), 2005)
Electronic portfolios [ePortfolios] are a recent addition to the language of higher education. Commencing with a summary of their role from EDUCAUSE, whose mission is to advance higher education by promoting the intelligent use of information technology, the distinctive characteristics of ePortfolios are outlined and salient differences from conventional portfolios in terms of process and outcomes are explored. Having considered the attributes of a mature ePortfolio, the paper focuses on pedagogical and technological issues for students and staff to move to mature ePortfolios. While accepting the valuable role ePortfolios can play in higher education, and that students increasingly come to the tertiary sector with expectations and experience that appear to warrant this approach, the paper concludes that decision making in this area is not yet adequately supported by research. Educators need to be open to the promise ePortfolios offer their students and staff but be aware of the implications for their adoption.